2019
DOI: 10.1021/acscatal.9b02005
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Elusive 1,4-Reduction of Vinyl Epoxides through Copper Catalysis

Abstract: We present an efficient strategy for the formal 1,4-reduction of vinyl epoxides that does not require superstoichiometric amounts of a strong reductant. Using a readily available copper catalyst and a diboron compound, a wide variety of enantioenriched allylic alcohols has been prepared. Additionally, epoxyenynes have been reduced in a 1,4-manner to selectively afford skipped enynes or skipped dienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In 2019, the Tortosa lab utilized similar S N -type reactivity with epoxide electrophiles, developing a stereospecific cyclization affording control of four adjacent stereocenters (Scheme ). Building on their previous studies of borylcupration strategies with vinyl epoxides, , they found that styrene-based substrates avoided previously described 1,4-borylation. The optimized conditions accessed various substitutions of the aryl group on the alkene and achieved distinct diastereomers when employing different stereoisomers of the substrate ( 84a – c ).…”
Section: Alkylationmentioning
confidence: 99%
“…In 2019, the Tortosa lab utilized similar S N -type reactivity with epoxide electrophiles, developing a stereospecific cyclization affording control of four adjacent stereocenters (Scheme ). Building on their previous studies of borylcupration strategies with vinyl epoxides, , they found that styrene-based substrates avoided previously described 1,4-borylation. The optimized conditions accessed various substitutions of the aryl group on the alkene and achieved distinct diastereomers when employing different stereoisomers of the substrate ( 84a – c ).…”
Section: Alkylationmentioning
confidence: 99%
“…The research group of Miura reported an asymmetric aminoboration of oxa‐ and azabicyclic alkenes with diboron reagents [B 2 pin 2 , Bpin‐Bdan (dan=1,8‐diaminonaphthalenyl)] and O ‐benzoyl‐hydroxylamines under copper catalysis while maintaining the bicyclic framework [83] . Very recently, Tortosa and co‐workers reported a couple of striking examples of the potentiality of copper‐boryl complexes in organic synthesis [84,85] . They discovered that aryl substituted vinylepoxides (such as A , Scheme 23) after initial regioselective carboboration to give intermediate B , undergo an intramolecular S N 2 type reaction to afford stereospecifically cyclopropylboronate D [84] .…”
Section: Diboron Compounds and Silaboranesmentioning
confidence: 99%
“…Alternatively, if intermediate B is intercepted by protonolysis before cyclization, the corresponding epoxy boronate F undergoes base‐promoted β‐oxygen elimination to give a formal reduction product (Scheme 24). [85] …”
Section: Diboron Compounds and Silaboranesmentioning
confidence: 99%
“…Other methods rely on the selective creation of the C-O bond, such as the addition of Nhydroxyphthalimide to allenes [12], or the C-H bond, through the metal-catalyzed reduction of enones [13][14][15] or vinyl epoxides [16]. Other procedures involve the metal-or organocatalyzed isomerization of oxiranes [17] and the kinetic resolution of racemic allylic alcohols [18,19].…”
Section: Introductionmentioning
confidence: 99%